Adherence to the Danish food-based dietary guidelines and risk of myocardial infarction: a cohort study. Issue 7 (14th January 2018) - Hansen, Camilla Plambeck; Overvad, Kim; Tetens, Inge; Tjønneland, Anne; Parner, Erik Thorlund; Jakobsen, Marianne Uhre; Dahm, Christina Catherine
Abstract: Objective: A direct way to evaluate food-based dietary guidelines is to assess if adherence is associated with development of non-communicable diseases. Thus, the objective was to develop an index to assess adherence to the 2013 Danish food-based dietary guidelines and to investigate the association between adherence to the index and risk of myocardial infarction (MI). Design: Population-based cohort study with recruitment of participants in 1993–1997. Information on dietary intake was collected at baseline using an FFQ and an index ranging from 0 to 6 points was created to assess adherence to the 2013 Danish food-based dietary guidelines. MI cases were identified by record linkage to the Danish National Patient Register and the Causes of Death Register. Cox proportional hazards models were used to estimate hazard ratios (HR) of MI. Setting: Greater areas of Aarhus and Copenhagen, Denmark. Subjects: Men and women aged 50–64 years ( n 55 021) from the Diet, Cancer and Health study. Results: A total of 3046 participants were diagnosed with first-time MI during a median follow-up of 16·9 years. A higher Danish Dietary Guidelines Index score was associated with a lower risk of MI. After adjustment for potential confounders, the hazard of MI was 13 % lower among men with a score of 3–<4 (HR=0·87; 95 % CI 0·78, 0·96) compared with men with a score of <3. The corresponding HR among women was 0·76 (95 % CI 0·63, 0·93). Conclusions: Adherence to the 2013 Danish food-based dietary guidelines was inversely associated with risk of MI.